EFEKTIVITAS PERAN KOMITE SEKOLAH DI SD NEGERI 1 KEBUMEN KECAMATAN SUKOREJO KABUPATEN KENDAL - Sadewa, Erfan Yusuf; Yuniningsih, Tri (Journal of Public Policy and Management Review, 2016)
Most of professionals assume that The education system which is so far has been managed in bureaucratic and centralist represents as one of the reasons of the low educations quality in Indonesia. The forming of School's committee is considered as a solution because it play a role as the consultant on determinant of educational policy in the Institute. Nevertheless, the school's comitte still workless and un optimally yet of its role.The purpose of this research is to describe and to analyze, does the role of school’s comittee at SD Negeri 1 Kebumen, Sukorejo District, Kendal Regency is effective enough, and to identify the obstacles in the effectiveness of school's committee role at SD Ngerei 1 Kebumen, Sukorejo District, Kendal Regency. This research uses a descriptive type and qualitative approach. The data collection techniques are such as observation, interview, documentation, and literature study. The result of this research shows that the effectiveness of the school's comittee role at SD Negeri 1 Kebumen is overall effective. The school's comittee roles that still workless are The supporting agency role and The controlling agency role. Recommended to fix the supporting agency role there are some ways such as by socialize to student’s parents/guardians about the importance of meeting and opinion polling, the school’s comitee be expected to do a more comprehensive relation, keep in touch with the upper middle society and business to contribute enhance the education quality. Furthermore, to fix the controlling agency role is suggested to keep in touch in a good communication with any part of school’s components, especially comittee’s organizer and school to be together enhance the education quality at SD Negeri 1 Kebumen.